Evaluation of Online Optometry Learning Programs and Webinars During Covid-19 Lockdown in India - Post-One Year of Lockdown Period: Outcomes of a Survey. - Usgaonkar, Ugam P. S.; Bind, Avantika; Shetty, Aksha (Optometry & Visual Performance, 2023)
Background: In late 2019, in response to the worldwide spread of the disease COVID-19, the authorities of India ordered a nationwide lockdown, which extended through 2021. In the wake of the pandemic, optometric education faced massive changes. This study aimed to evaluate the impact of online learning platforms from the student's perspective on the benefits and difficulties encountered. Methods: An online survey was conducted for students of optometry across India. A list of colleges was made that provided the B.OPT/M.OPT degrees and fellowships in different specialties. The questionnaire was circulated to the colleges through e-mail and multiple social media platforms (LinkedIn, WhatsApp, and Instagram). The survey requested demographic information and details related to different online learning programs and the status of education provided during the COVID-19 pandemic. Results: A total of 465 questionnaires were circulated, and 237 (50.96%) completed responses were received. The average age of students was 21.9 ± 2.14 years. The majority of the respondents (82.2%) were enrolled in bachelor's degree in optometry, 15.1% were in Masters in Optometry/M. Phil. programs, 1.68% were pursuing a Diploma in Optometry program, and 0.8% of the respondents were in fellowship. About 87.7% of the students responded that the lockdown had negatively impacted their learning programs. Ninety-seven percent of students responded that their college/university faculty were providing online lectures. The students responded that they faced difficulties in attending online lectures: 79% reported having network and connectivity issues, and 8% had electricity fluctuation issues. In all, 71.7% of the respondents felt that online classes and webinars were useful during the lockdown period. Conclusion: Optometry students believed that online lectures were useful. There was a rise in online learning platforms to gain knowledge. Some students faced difficulty in attending lectures where internet-related connectivity issues were the common complaints. Optometry students and practitioners have adapted quickly to the pandemic with all vital precautions.